The Supremacy of the Constitution of the Federal Republic of Nigeria 1999 (As Amended): A Myth or Reality? - Jimoh, Saliu (ABUAD Law Journal, 2021)
Realistically speaking, the rate at which Nigerians, both high and low, trampled upon the provisions of the constitution in their daily doings, and with impunity for that matter leaves much to be desired. Can we, with all sense of responsibility, say that the provisions of the Constitution of the Federal Republic of Nigeria 1999 as amended are sacrosanct and most respected by all its subjects as codified? Are these provisions cosmetic or reality? The research employed doctrinal research methodology by analysing primary and secondary sources of data and texts. The research found that this issue is very pivotal and of jurisprudential importance to constitutional development in Nigeria and there is therefore an imperative need to make radical contribution to the subject matter through critical thinking and practical analysis of realities on ground vis- a-vis what is obtainable in an ideal constitutional democracy. It concludes that If the Supremacy of the constitution will move from being a mere farce to a real deal, the organs of government, especially the Executive and the Legislature have to respect the spirit and letter of the constitution.